The role of social sustainability in building assessment. Issue 5 (4th July 2019) - Stender, Marie; Walter, Annette
ABSTRACT: Can social sustainability be built? What are the challenges and potential for incorporating the concept of social sustainability into the assessment of building projects? Theoretical approaches to social sustainability are examined for the ways it is applied in practice by building industry stakeholders. A fundamental question is whether and how social sustainability can be measured, assessed and certified in the construction or renewal of housing and neighbourhoods. In addition to physical and functional indicators, it is suggested that certification systems ( e.g. the Deutsche Gesellschaft für Nachhaltiges Bauen – DGNB) should also reward social initiatives. A framework was developed involving 12 indicators grouped three overarching themes: social cohesion; participatory processes; and accessibility to living opportunities. A collaborative case study project involving two Danish social housing neighbourhoods examines how social sustainability indicators could be integrated into the application of certification systems such as the DGNB and whether the certification system can be improved by integrating social and organizational aspects with the existing criteria for physical and functional layout. It is found that certifications must take the housing complex or neighbourhood's relationship with the surrounding city into account, as well as its development over time and flexibility towards future needs.